An assessment of quality of randomized controlled trials in shoulder instability surgery using a modification of the clear CLEAR-NPT score - Alkaduhimi, Hassanin (Shoulder Elbow, 2018)
BACKGROUND: The present study aimed to evaluate the methodological quality and determine the quality of reporting of randomized controlled trials (RCTs) that assess surgical treatment for shoulder instability. METHODS: A Cochrane, Pubmed, EMBASE and Trip database search was performed, including the relevant literature, regarding RCTs that report on shoulder instability published between January 1994 and January 2017. Methodological quality was assessed with a modification of the Checklist to Evaluate A Report of a Nonpharmacologic Trial (CLEAR-NPT). Points were assigned based on 18 items regarding patient characteristics, randomization, care provider characteristics, surgical details and blinding, with a total score ranging from 0 points to 18 points. Missing items were verified with the corresponding authors of the studies. Quality of reporting corresponds to the total scores including the items that were additionally provided by the authors. RESULTS: We included 22 studies. Of these, nine corresponding authors provided additional information. The average methodological quality was 16.9 points (11 studies) and the average quality of reporting was 9.5 points (22 studies). Items scoring worst included information regarding the surgeon’s experience, the patients’ level of activity, comorbidities, analyzing according to ‘intention-to-treat’ principles, and blinding of care providers, participants and assessors. CONCLUSIONS: RCTs reporting on shoulder instability surgery are well performed but poorly reported.